Pengaruh Model Project Based Learning (PjBL) Terhadap Sikap Peduli Lingkungan Siswa Kelas V di SDN Kota Bengkulu - Silaban, Harri; Noperman, Feri; Amaliyah, Yuli (JURIDIKDAS (Jurnal Riset Pendidikan Dasar), 2025)
This study aims to determine the effect of using the Project Based Learning (PjBL) model on the environmental care attitude of fifth-grade students in elementary schools in Bengkulu City. This research employed a quantitative approach with a quasi-experimental method and a Matching Only Pretest-Posttest Group Design. The research population included SDN 69, SDN 71, SDN 72, SDN 88, SDN 89, and SDN 103 in Bengkulu City. The sample consisted of fifth-grade students from SDN 69 (experimental group) and SDN 71 (control group). The instrument used was a questionnaire on environmental care attitudes administered through pretests and posttests. Data were analyzed using descriptive statistics, prerequisite tests, and t-tests. The results showed that the t-count (2,807) > t-table (2,004) and the Sig. (2-tailed) value of 0,007 < 0,05. The average score of environmental care attitude in the experimental group was 44,10, while the control group scored 40,88. This indicates a significant difference in posttest results between the two groups, caused by the different treatments. The experimental class applied the PjBL model with a real project such as ecobrick making, which provided hands-on experience and was more effective in shaping environmental care attitudes compared to the control class that only used the PBL model without a real project. Thus, it can be concluded that the PjBL model has an effect on the environmental care attitude of fifth-grade students in elementary schools in Bengkulu City.